Broken bars fault diagnosis based on uncertainty bounds violation for three‐phase induction motors. (18th December 2013) - Mustafa, Mohammed Obaid; Nikolakopoulos, George; Gustafsson, Thomas
Summary In this article, a novel fault diagnosis scheme, based on uncertainty bounds violation, is being presented for the case of broken bars in squirrel‐cage three‐phase induction motors. The fault diagnosis is performed in two steps. First, the parameters of the healthy induction motor are identified using a set membership identification approach, where corresponding uncertainty bounds are also being provided. Second, the proposed uncertainty bounds violation conditions for the fault diagnosis are evaluated online, on the converged identified model, during a sliding time window. Multiple simulation results are presented that demonstrate the efficacy of the proposed scheme toward fault detection and diagnosis among different numbers of broken bars. Copyright © 2013 John Wiley & Sons, Ltd.